1993
DOI: 10.1002/jso.2930520405
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative radiation, surgical margins, and local control of extremity sarcomas of soft tissues

Abstract: The relationship between status of the surgical margin and local control of soft tissue sarcoma of the extremities by preoperative radiation therapy has been assessed in 132 consecutive patients from 1974 to 1988. The 5-year actuarial local control rate was 94% for all patients; the rates were 97% and 82% for the 104 tumors with negative margins and the 28 tumors with positive margins, respectively. The local control rate was independent of the extent of the negative margin. For primary sarcomas, the local con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
108
5
6

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(127 citation statements)
references
References 26 publications
(20 reference statements)
8
108
5
6
Order By: Relevance
“…Although we didn't find any significance for tumor size within the range of 5 cm multiples, it seems to be an independent prognostic factor for DFS when we reanalyze it regarding the median size. Positive surgical margin increases the local recurrence rate even in patients with combined surgery and radiotherapy (Rosenberg et al, 1982;Sadoski et al, 1993;Pisters et al, 1996;Zagars et al, 2003). In our series, there were 19 patients with positive margin after resection.…”
Section: 1775 Preoperative Radiotherapy With or Without Chemotherapymentioning
confidence: 50%
See 1 more Smart Citation
“…Although we didn't find any significance for tumor size within the range of 5 cm multiples, it seems to be an independent prognostic factor for DFS when we reanalyze it regarding the median size. Positive surgical margin increases the local recurrence rate even in patients with combined surgery and radiotherapy (Rosenberg et al, 1982;Sadoski et al, 1993;Pisters et al, 1996;Zagars et al, 2003). In our series, there were 19 patients with positive margin after resection.…”
Section: 1775 Preoperative Radiotherapy With or Without Chemotherapymentioning
confidence: 50%
“…Easier tumor delineation and eradication of microscopic tumor seeding are the other advantageous of preoperative radiotherapy. Although wound complications are reported more in the patients treated by means of preoperative treatment than the patients treated by postoperative radiotherapy, less late toxicity were seen compared with postoperative radiotherapy in the long-term follow-up analysis (Suit et al, 1985;Nielsen et al, 1991;Sadoski et al, 1993;O'Sullivan et al, 2002;Davis et al, 2005). Furthermore, delay of adjuvant radiotherapy due to wound healing after surgery is prevented by using radiotherapy in the preoperative setting.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] In our study, we observed significantly higher margin-negative resection rates in the patients who had a radiographic response than in those who had no response. Although reports in the literature on the impact of tumor size on local control have been mixed, [11][12][13][14] higher rates of radiographic response in patients with smaller tumors (Յ 11.5 cm) may have contributed to the better local control observed in the patients who had any radiographic response.…”
mentioning
confidence: 68%
“…Second, they maintain that lower doses of radiation can more easily be delivered preoperatively to an undisturbed tumor bed, which may also have improved tissue oxygenation. 46,51,52 Third, the preoperative radiation fields can be smaller and the number of joints included in those fields fewer than those in postoperative radiation fields, which may result in an improved functional outcome. 53 And finally, advocates of preoperative radiation therapy contend that by shrinking the tumor, radiation therapy can facilitate surgical resection.…”
Section: Radiation Therapymentioning
confidence: 99%